Ethnicity, Markets, and Migration in the Andes : At the Crossroads of History and Anthropology - Tandeter, Enrique; Harris, Olivia; Larson, Brooke (Book collections on Project MUSE., 1995)
"Major compilation of historical and anthropological articles focuses on the nature of markets and exchange structures in the Andes. Prominent scholars explore Andean participation in the European market structure, the influence of migration in changing ethnic boundaries and spheres of exchange, and the politics of market exchange during the colonial period. Larson's introduction places articles within the context of Andean economic systems, while Harris concludes with an appreciation of the relationships between mestizo and indigenous ethnic identities in the context of market relations. Both introduction and conclusion lend a greater coherence to this carefully-crafted and monumental volume"--Handbook of Latin American Studies, v. 57.